Research Progress of Cell Lineage Tracing and Single-Cell Sequencing Technology in Malignant Skin Tumors - Li, Ang; Liu, Baoyi; Xu, Jingkai; Cui, Yong (Frontiers in Surgery, 2022)
Cell lineage tracing and single cell sequencing have been widely applied in development biology and oncology to reveal the molecular mechanisms in multiple basic biological processes and the differentiation of stem cells, as well as quantify the differences between single cells. They provide new methods for in-depth understanding of the origin of tumors, the heterogeneity of tumor cells, and the drug resistance mechanism of tumors, thus inspiring new strategies for tumor treatment. In this review, we summarized the progress of cell lineage tracing technology and single-cell sequencing technology in the research of malignant melanoma and cutaneous squamous cell carcinoma, attempting to spark new ideas for further research on skin tumors.